Erotic capital as a component of the relational capital of organization - Syper-Jędrzejak, Marzena (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The article is devoted to the erotic capital of employees treated as part of relational capital. The purpose of the paper is to show that employees’ erotic capital can currently constitute a competitive advantage of a company, and considerations on it should not be limited to an individual perspective (treating erotic capital only as a factor of personal success). There is generally a lack of studies devoted to this issue in Polish literature. The article is exploratory and theoretical. It was created on the basis of an analysis of available publications with erotic capital sought by the snowball method. It has been established that in the organizational perspective, erotic capital is of particular importance for establishing and maintaining relationships with clients and representing the company.